2020
DOI: 10.25259/jcis_153_2019
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of intraluminal stent enhancement in estimating coronary in-stent restenosis

Abstract: Objective: In-stent restenosis (ISR) diagnosis is among the most serious complications of patients undergone stent implantation. Although coronary computed tomography angiography (CCTA) has been widely used for ISR assessing, stent narrow lumen and presence of stent’s struts artifacts have limited its efficacy. The use of quantitative techniques may provide more valuable findings for ISR diagnosis. The aim of this study is to assess the predictive value of a quantitative technique of ISR estimation based on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, in-stent restenosis (ISR) remains a significant challenge for patients undergoing PCI [3]. It was reported that there were about 10% of patients develop ISR [4,5]. In recent years, a number of in vitro and in vivo studies have identified some potential causes of ISR, including stent gap, residual uncovered atherosclerotic plaques and polymer damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, in-stent restenosis (ISR) remains a significant challenge for patients undergoing PCI [3]. It was reported that there were about 10% of patients develop ISR [4,5]. In recent years, a number of in vitro and in vivo studies have identified some potential causes of ISR, including stent gap, residual uncovered atherosclerotic plaques and polymer damage.…”
Section: Introductionmentioning
confidence: 99%
“…[3] However, there are clinical limitations of stent placement such as corrosion processes and in-stent restenosis (ISR) formation. [4][5][6] Due to the risk of allergenic or cytotoxic species' release such as Ni, Co, Cr, or Al through the body, biomaterials have been developing considering their corrosion resistance. [7,8] DOI: 10.1002/adts.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] DOI: 10.1002/adts. 202100626 Blood tissue has an electrolytic feature because of the cation contents including H + , K + Na + , Ca 2+ , and Mg 2+ , and the anion contents including OH -, HCO 3 -, Cl -, PO 4 3-, and SO 4 2-. [9] Negatively and positively charged species in a flowing blood tissue cause implanted biomaterial and body fluid to have different electrical potentials.…”
Section: Introductionmentioning
confidence: 99%
“…If both have severe or tandem calcifications and stents, performance of coronary computed tomography angiography (CCTA) further reduced. [4][5][6] The gold standard for the evaluation of in-stent restenosis (ISR) in clinical is invasive coronary angiography (ICA). However, most of patients are willing to have non-invasively and efficiently assessment of ISR.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, patients previously treated with stent often have high possibilities to show atherosclerotic burden of non-treated coronary segments. If both have severe or tandem calcifications and stents, performance of coronary computed tomography angiography (CCTA) further reduced [4–6] . The gold standard for the evaluation of in-stent restenosis (ISR) in clinical is invasive coronary angiography (ICA).…”
Section: Introductionmentioning
confidence: 99%